Susceptibility of Antarctic krill (Euphausia superba Dana) to ultraviolet radiation - Newman, SJ; Nicol, S; Ritz, DA; Marchant, H (Polar Biology, 1999)
We irradiated captive juvenile Euphausia superba in the laboratory with lower than spring surface levels of ultraviolet-B, ultraviolet-A and photosynthetically active radiation, in order to examine their response in terms of mortality and generalised activity. Levels of photosynthetically active radiation 3-5 times below surface irradiance caused krill to die within a week, while animals in the dark survived. Addition of ultraviolet-B typical of depths up to 15 m were found to significantly accelerate mortality and lead to a drop in activity in all experiments. A drop in activity in krill exposed to ultraviolet-A wavelengths was evident without an increase in mortality. The protein content of animals from various treatments was found not to vary.